The Impact of Organic Vegetable growing Project to Household’s Income generation of residents in Kaisone Phomvihan City, Savannakhet Province Thongsa TOUNMANYSONE*, Khoune SACKBOUAVONG, Lidsada BANMANIVONG, Vannasinh MANIVONG, Phetviengsavanh PHOUMPHAKDY - MANIVONG, Vannasinh; PHOUMPHAKDY, Phetviengsavanh; SACKBOUAVONG, Khoune; BANMANIVONG, Lidsada; TOUNMANYSONE, Thongsa (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objective of this study was to estimate the impact of Organic Vegetable Growing Project (OVGP) on household’s income generation of residents in Kaisone Phomvihan City, Savannakhet Province, We use cross-sectional data that is collected from a sample of 313 households in the Kaisone Phomvihanh City, Savannakhet Province in 2020, the estimate is used regression model (Ordinary Least Square: OLS) and the econometric analysis is based on the model constructed by An and Richard (2015). The results of the study founds the average income from organic vegetable growing is higher than average income from other agriculture activities about 2.11 times, the OVGP has a positive impact on household’s income generation and the impact is statistically significant, The significant factors as an impact the household’s income generation ranging from gender, education, land for agriculture, ownership of land and participation, because they have statistically positive impact on household’s income generation. Therefore, Policy maker should be aware the promotion of OVGP that have significant impacts on poverty reduction strategy of Lao PDR. It is the first paper try to investigate the impact of the OVGP on household’s income in Savannakhet province, Lao PDR.